Temporal Discounting and Search Habits: Evidence for a Task-Dependent Relationship - Khaw, Mel W.; Li, Ziang; Woodford, Michael (Frontiers in Psychology, 2018)
Recent experiments suggest that search direction causally affects the discounted valuation of delayed payoffs. Comparisons between options can increase individuals’ patience toward future payoff options, while searching within options instead promotes impatient choices. We further test the robustness and specificity of this relationship using a novel choice task. Here individuals choose between pairs of delayed payoffs instead of single delayed outcomes. We observe a relationship between search styles and temporal discounting that are the opposite of those previously reported. Integrators – those who tend to compare attributes within alternatives – discount and choose more slowly than comparators – those who are more likely to compare between alternatives. This finding supports and augments the view that individuals’ search strategy is predictive of subsequent discount rates. In particular, the direction of this relationship is further modifiable based on the spatial layout and varying information within an individual’s decision-making environment.